2018
DOI: 10.1016/j.envres.2018.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Residential proximity to agricultural fumigant use and respiratory health in 7-year old children

Abstract: Residential proximity to agricultural fumigant use during pregnancy and childhood did not adversely affect respiratory health in the children through 7 years of age. These findings should be explored in larger studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…Childhood respiratory symptoms, asthma prevalence and pulmonary function changes were associated with elemental sulfur applications within 0.5 and 1 km radii of the residence [42], but non-significant associations were observed for residential proximity to fumigants used in the same cohort [43]. Furthermore, one study explored the children's school proximity to the cultivation areas with pesticide use and respiratory effects, and found that urinary CM metabolite levels (by ETU concentration) were significantly associated with an increased risk of asthma and rhinitis [44].…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Childhood respiratory symptoms, asthma prevalence and pulmonary function changes were associated with elemental sulfur applications within 0.5 and 1 km radii of the residence [42], but non-significant associations were observed for residential proximity to fumigants used in the same cohort [43]. Furthermore, one study explored the children's school proximity to the cultivation areas with pesticide use and respiratory effects, and found that urinary CM metabolite levels (by ETU concentration) were significantly associated with an increased risk of asthma and rhinitis [44].…”
Section: Resultsmentioning
confidence: 89%
“…A population-based study in U.S. did not observe clear associations between asthma and OP and OC exposure (which was measured using biomarkers of DAP or DDT insecticides) among school-aged children [21]. No significant associations were observed between residential proximity to fumigant use during pregnancy and from birth to age 7 (assessed through the pesticide use registration in California) and respiratory symptoms, use of asthma medication, and lung function measurements [43].…”
Section: Resultsmentioning
confidence: 92%
“…In support of a link between pesticide exposure and ASD, the Childhood Autism Risks from Genetics and Environment (CHARGE) study found a positive association between ASD and residential proximity to OP application during the second and third trimester of gestation in a population-based case control study in California [47]. In addition to ASD, deficits in cognition and attention were associated with residential proximity to OP use during gestation in the Center for the Health Assessment of Mothers and Children of Salinas (CHAMACOS) Study in the Salinas Valley, California [17]. The level of OP metabolites in maternal urine during pregnancy was associated with deficits in social reciprocal behavior, which were more prominent in boys than girls in the Mount Sinai Children’s Environmental Health Center study [14].…”
Section: Introductionmentioning
confidence: 99%
“…The few pesticide-respiratory health effect studies among children adopt the single-pollutant approach, and have shown both negative and null effects of pesticide exposure on lung function. 6,61,62 For example, a study by Raanan et al provides evidence of significant FEV 1 and FVC decreases with early life exposures to organophosphate pesticide in 7-year-old children in the Center for the Health Assessment of Mothers and Children of Salinas (CHAMACOS) study. 6 However, the authors explored early life exposure windows of children with no asthma, only in single-pollutant analyses.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, another study on children from the same CHAMACOS cohort showed that exposure to agricultural fumigants including MeBr resulted in no adverse respiratory effects. 61 The authors again only conducted single-pollutant analyses, and do not explore complex and nonlinear synergistic effects that likely exist between other environmental exposures within and outside the domain of pesticides.…”
Section: Discussionmentioning
confidence: 99%